2021
DOI: 10.1101/2021.02.27.433180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negligible impact of SARS-CoV-2 variants on CD4+and CD8+T cell reactivity in COVID-19 exposed donors and vaccinees

Abstract: The emergence of SARS-CoV-2 variants highlighted the need to better understand adaptive immune responses to this virus. It is important to address whether also CD4+ and CD8+ T cell responses are affected, because of the role they play in disease resolution and modulation of COVID-19 disease severity. Here we performed a comprehensive analysis of SARS-CoV-2-specific CD4+ and CD8+ T cell responses from COVID-19 co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
161
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(184 citation statements)
references
References 73 publications
21
161
0
2
Order By: Relevance
“…current VOC (B.1.1.7 and B.1.351). This data is compatible with a recent preprint report that the epitope sequences of the vast majority of SARS-CoV-2 T cell epitopes are not affected by the mutations found in the B.1.1.7 or B.1.351 variants40 , with no signi cant differences observed in CD4 and CD8 responses to a pool of S peptides corresponding to the ancestral sequence and those corresponding to the different variants. T cell responses to SARS-CoV-2 are known to target a wide range of regions in spike41 .…”
supporting
confidence: 92%
“…current VOC (B.1.1.7 and B.1.351). This data is compatible with a recent preprint report that the epitope sequences of the vast majority of SARS-CoV-2 T cell epitopes are not affected by the mutations found in the B.1.1.7 or B.1.351 variants40 , with no signi cant differences observed in CD4 and CD8 responses to a pool of S peptides corresponding to the ancestral sequence and those corresponding to the different variants. T cell responses to SARS-CoV-2 are known to target a wide range of regions in spike41 .…”
supporting
confidence: 92%
“…Limited data on the immunological determinants of protection are available, however recent data from rhesus macaques indicate that relatively low neutralizing antibody titers are sufficient for protection against SARS-CoV-2, and that cellular immune responses may contribute to protection if antibody responses are suboptimal 21 . Induction of binding and neutralizing antibodies as well as SARS-CoV-2 cellular spike protein-specific T cell responses after vaccination have been reported 22,23 and most SARS-CoV-2 specific T cell epitopes in both convalescent and vaccinated individuals are not affected by the AA substitutions found in the spike protein of the B.1.1.7 and B.1.351 variants 24 . Protection against severe COVID-19 disease might be mediated by T cells and would therefore not be different between the current variants.…”
Section: Mainmentioning
confidence: 94%
“…In addition to neutralising and binding antibodies, SARS-CoV-2 infection also elicits a vast repertoire of T cell responses and dominant epitopes had the capacity to bind multiple HLA allelic variants [22]. A further study by the same authors found that "CD4+ and CD8+ T cell responses in convalescent COVID-19 subjects or COVID-19 mRNA vaccinees are not substantially affected by mutations found in the SARS-CoV-2 variants" [23]. A major limitation of that study is that all donors were recruited in California and had no known exposure to the escape variants first found in the UK, South Africa or Brazil.…”
Section: Cell Binding and Functional Immunitymentioning
confidence: 99%